Impact Organization Culture and Perceived Organization Support on Creativity of High School Teachers - Umiarti Umiarti; Yetty Supriyati; Billy Tunas (AIBPM Publisher, 2019)
In general, teacher creativity has a main function that helps get the job done quickly and efficiently. The purpose of this study is to conduct a study to determine the direct effects of organization culture and Perceptions of organizational support for the creativity of high school teachers. This study used 165 high school teachers in Indonesia. The results show that organization culture has a significant and positive effect on creativity by 0.629. Perceived organization support also has a significant and positive effect on creativity by 0.389. The implications of this research to be able to improve the creativity of teachers, every schools in Indonesia need a strong organizational culture and support from the organization.